Simulasi Waduk Sukaraja III, Kecamatan Margatiga, Kabupaten Lampung Timur - Febrian, Febrian; Susilo, Gatot Eko; Wahono, Endro P (Universitas Lampung, 2016)
Sukaraja III’s reservoir is one of reservoir that is usefull to irrigate rice fields in Rawa Sragi II. To optimize inflow and storage of Sukaraja III’s reservoir, simulation is needed to obtain how many area can be irrigated by optimize the objection function of reservoir.This study was conducted at Sukaraja village, and Negeri Jemanten, Margatiga District, East Lampung Regency. In this study, there’re three analysis, analysis of inflow, analysis of outflow and analysis about water balance. Analysis of inflow use Argoguruh’s weir discharge data 2005-2012. Analysis of inflow include Argoguruh’s weir runoff discharge and discharge of watershed Sukaraja III’s dam. Analysis of inflow include evaporation, maintenance flow, and water needs of the irrigation. Analysis about water balance is used to know how much the volume of reservoir which affected by inflow and outflow. Next, do the simulation to get the maximum area of field with meet two requirements. Reservoir water level should always be above 18 meters and must meet 80% reliability.From the analysis, the result for the largest total inflow in 2005 and the smallest total inflow occurred in 2006. Outflow for each year is different because it is influenced by planting different beginning period, the beginning of January and the beginning of December, and evaporation which caused by total area of reservoir inundation. Fields which can be irrigated with initial period of planting in early January is 4739 ha, and fields which can be irrigated with initial period of planting in early December is 5600 ha. This simulation meets 100% reliability and reservoir water level is always above 18 meters. Key word: simulation, inflow, outflow